The comparison in terms of trust of modern and traditional supply chains in fresh fruit and vegetable - Ebru Seckin (European Regional Science Association (ERSA), 2013)
During the 1990s transition period in developed countries, the retail sector was privatized and some domestic-capital supermarket chains gradually emerged. Supermarkets have restructured their procurement strategies through the introduction of private standards, centralized procurement systems and distribution centers. Recent studies have shown a meteoric rise of supermarkets in Latin America in the past two decade (Reardon and Berdegue, 2002; Reardon et al; 2003), with profound effects on agrifood systems via important changes in organization and institutions, including centralization of procurement from farmers, decline of traditional wholesale systems, and demanding private standards on product quality and safety. Despite the increase in agri-food commodities emanating from the expansion of the retail sector, there have been little or no opportunities for smallholder farmers. Agri-food markets are restructuring as supermarkets continue to expand. The restructuring process is likely to exclude farmers from food markets in two ways; firstly through displacement of traditional markets by formal food chains; and secondly, the restructuring process will exclude farmers through the introduction of private standards. There has been literature in the retail system, and agri-food industry transformation and how pre-transition conditions in the retail sector conditions in the retail sector conditioned the development path of the sector after the transition (Dries, Reardon, Swinnen, 2006) Research question is how have been small farmers effected by supermarkets which have been a part in supply chain of food sector. The aim of this paper is to determine the typologies of the different supply chain in the agri-food industry (restructuring of the sectors and procurement system modernization by companies in the restructured sectors) and its impacts on farmers. this paper has three sub-goals mentioned below: ? to examine the strategies of the different supply chain in the fresh fruit and vegetable. The organizational changes in the fresh fruit and vegetables procurement systems of supermarket and the wholesale in the Ýstanbul ? to comprehend the geography of the relational network from farm to consumer, and the network between supermarket and other actors in supply chain for fresh vegetable and fruit. ? to determine its impacts on farmers: The characteristics of restructuring procurement systems and its effects on small farmers will be revealed. The necessary conditions will be described for including of small farmers to restructuring food supply chain.
Keywords: 330; food industry; supermarkets; supply chain; small farmer; retail sector; fresh vegetable and fruit